Animals and agency an interdisciplinary exploration - Sarah E. McFarland; Ryan Hedige (Human-animal studies, 2009)
This collection examines the question of nonhuman animal agency by shifting emphasis from the human perspective toward that of other animals, exploring modes of animal resistance to human behaviors, and considering the ways the presence of animals refracts human notions like agency and species.